Value of bone marrow biopsy in Hodgkin lymphoma patients staged by FDG PET: results from the German Hodgkin Study Group trials HD16, HD17, and HD18. (13th July 2018) - Voltin, C -A; Goergen, H; Baues, C; Fuchs, M; Mettler, J; Kreissl, S; Oertl, J; Klaeser, B; Moccia, A; Drzezga, A; Engert, A; Borchmann, P; et al.
Abstract: Background: Bone marrow (BM) involvement defines advanced-stage Hodgkin lymphoma and thus has impact on the assignment to treatment. Our aim was to evaluate whether the established BM biopsy may be omitted in patients if 18 F-fluorodeoxyglucose positron emission tomography (PET) scanning is carried out during staging. Patients and methods: Our analysis set consisted of 832 Hodgkin lymphoma patients from the German Hodgkin Study Group trials HD16, HD17, and HD18 who underwent both PET scanning and BM biopsy before treatment. All PET studies were centrally reviewed and BM was categorized as showing focal involvement or not. Results: Taking BM biopsy as reference standard, baseline PET showed a negative predictive value of 99.9% [95% confidence interval (CI) 99.2% to 100%] with true-negative results in 702 of 703 cases. The sensitivity of PET for detecting BM involvement was 95.0% (95% CI 75.1% to 99.9%) as it could identify 19 out of 20 patients with positive BM biopsy. Moreover, PET found 110 additional subjects with focal BM lesions who would have been considered negative by biopsy. Conclusions: When compared with BM biopsy, PET was able to detect focal BM lesions in a large number of additional patients. This indicates that conventional BM biopsy may substantially underestimate the actual incidence of BM involvement. Given the high negative predictive value, baseline PET scanning can safely be used to exclude BM involvement in Hodgkin lymphoma. BM biopsy should be considered only in such patients in whom PET-detected lesions lead to a change of treatment protocol. Registered trials: The trials included in this analysis were registered at ClinicalTrials.gov: HD16—NCT00736320, HD17—NCT01356680, and HD18—NCT00515554.